Effect of vitamin D, calcium and multiple micronutrients supplementation on lipid profile in pre-menopausal Bangladeshi garment factory workers with hypovitaminosis D - Islam, Md Zahirul; Shamim, Abu Ahmed; Viljakainen, Heli T; Lamberg-Allardt, Christel; Jehan, Atia H; Khan, Habib Ullah; Al-Arif, Ferdaus Ahmad; Akhtaruzzaman, Mohammad (© 2014 International Center for Diarrhoeal Disease Research, 2017)
This article was published in the Journal of Health, Population and Nutrition [© 2014 International Center for Diarrhoeal Disease Research] and The Journal's website is at: https://www.ncbi.nlm.nih.gov/pubmed/25895202